A review of nucleate pool-boiling heat transfer in different liquids and nanofluids - Zarrag K.Z.; Ismail F.B.; Sann T.E.; Habeeb L.J. (SAGE Publications Ltd, 2024)
The goal of this review is to examine the current state of the art in nucleate pool boiling heat transfer in a variety of different fluids. The review is divided into many sections that discuss heat transfer in pool boiling, such as pool boiling of nanofluids, boiling behavior of waterglycerin combinations, and operational parameters. With the appropriate mixes of hydrocarbons and other commercial liquids, higher heat transfer coefficients may be produced. Coatings of nanoparticles with varying layer thicknesses applied to the heater surface may be optimized to improve heat transfer from the pool to the surrounding water. The heat transfer hypothesis elucidates the peculiarities of each pools boiling regime. It is also possible to expand it to flow boiling by combining pool boiling liquid motion with external mechanical force. Other phase transitions, such as condensation, solidification, and melting, can also be described using boiling heat flow processes. Pool boiling performance can be improved by making a variety of adjustments to the heating surfaces as well as by using pure liquids in the water. Improvements can be made to boiling parameters such as the heat flux, the critical heat flux, the heat transfer coefficient, bubble development and departure, and so forth. A nanoparticle addition to a pure liquid or a surface coating on a heating surface can improve heat transfer and boiling properties by increasing the surface area of the liquid. Pool boiling critical heat flux was enhanced with Al2O3-water nano fluid. Authors used three different powder sizes of Al2O3 which were 0.05, 0.3 and 1.0?m. Addition of alumina particle in water increases the boiling heat flux. Critical heat flux (CHF) was significantly enhanced using Titania and Alumina nano particles in water as compared to pure water. Average size of nano particle used was 85nm measured by scattering electron microscope. Enhancement in Critical heat flux is due to nano particle coating on heating surface. Characteristics of nucleate boiling are greatly affected by the operating pressure. Miniature flat heat pipe (MFHP) with evaporator having micro grooved heat transfer surface gives 50% increment in critical heat flux at atmosphere pressure whereas this value increases up to 150% at 7.4kPa pressure. The addition of CNT (carbon nanotube) to the base liquid increases the critical heat flux. Transmission electron microscopy confirms the average size of a nanoparticle as 15nm. Authors found that by decreasing pressure from atmosphere condition critical heat flux increases to 200% with CNT/water nano fluid as compared to deionized water. SiC-water nanofluids of 100nm size were experimented with at volume concentrations of 0.001%, 0.001%, and 0.01%. The size of the nanoparticle was confirmed by a scattering electron microscope. Authors concluded that at 0.01% of nano particle enhances critical heat flux to 105%. IMechE 2023.